THE URGENCY OF IMPLEMENTING FAITH EDUCATION IN CHILDREN - Atiko Nur Oktaviani; Muhammad Safwan Mabrur (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The decline in religious activity among young people in many countries and the influence of secularization in today's culture highlight the urgency of faith education. Data shows a trend of declining religious involvement among younger generations, and in some communities, the challenges of maintaining faith in an increasingly secular culture are becoming more pronounced. Harvey Cox proposed the concept of secularization as liberation from the influence of religion and metaphysical thought, with an emphasis on the difference between secularization and secularism. This approach creates space for a deeper understanding of religious values and the application of these values in everyday life. Faith education is the key to overcoming this challenge. In the Islamic context, faith education helps bridge the gap between secularization and religious values, enabling young generations to understand and integrate their beliefs in the context of an increasingly secular world. This approach is not just about replacing religion but rather about developing freer thinking in living the world.   Keywords: Islamic faith education, secularism, social problems